The Effect of Non-Cash Payments on the Money Supply in Indonesia During the Covid-19 Pandemic Period - Faza, Hamas; Tri Rahayu, Siti Aisyah; Hakim, Lukman (Future Science / FSH-PH Publications, 2023)
The development of non-cash payments is predicted to have an effect on real money demand, not only in Indonesia. The use of electronic money in Indonesia itself continues to increase especially in the covid-19 pandemic and it supported by technological developments. The purpose of this study was to analyse the effect of non-cash payments on real money demand in Indonesia. The method used is Vector Error Correction Model (VECM) using secondary data from Januari 2019 to December 2022. The independent variable is the amount of money circulated by Bank Indonesia, and the independent variables used are the value of debit / ATM card transactions, credit cards, and e -money. The results indicate that in the long run debit cards and e-money have a significant negative effect on money supply, while credit cards have positive effect on money supply but it’s not significan. While in the short term, all variables debit cards, credit cards and e-money are not significant on money supply.